Pemberian ASI Eksklusif dan Kejadian Diare pada Bayi di Puskesmas Umbulharjo 1 Yogyakarta Tahun 2016 - Ningsih, Ariana Norma; Wahyuningsih, Heni Puji; Margono, Margono (Poltekkes Kemenkes Yogyakarta, 2017)
Diarrhea disease is the second leading cause of infant morbidity and mortality. High incidence of diarrhea is affected by severalfactors, one of which is the absence of breastfeeding. The protective effect of breastfeeding is optimal if it is given exclusively. Thisresearch aims to identify the correlation between exclusive breastfeeding and incidence of diarrhea in babies at Puskesmas (PublicHealth Center) Umbulharjo I of Yogyakarta. It belongs an observational analytical research with historical cohort design. Thesample size was 84 consisting of 42 mothers with exclusive breastfeeding and 42 without exclusive breastfeeding who had babiesaged> 6-12 months from November to December 2016. Data were collected through interviews. Data were analyzed using chisquare, RR, cox regression. The results indicated that the incidence of diarrhea in babies who had a history of receiving exclusivebreastfeeding was 11.9% and in infants who did not receive exclusive breastfeeding was 35.7%. The results of the bivariateanalysis indicated that the factors related to the incidence of diarrhea were breastfeeding (p-value 0.010, RR 0.333), nutritionalstatus (p-value 0.003, RR 5.0) and occupation (p-value 0.048, RR 2.111). The rate of incidence of diarrhea in babies withoutexclusive breastfeeding was 27 of 100 babies/ month, which was higher than those with exclusive breastfeeding by 10 of 100babies/month. The multivariate analysis indicated that in regard to breastfeeding and occupation it was indicated thatbreastfeeding was the most influential factor in the incidence of diarrhea in babies (Coef B -1.059, p-value 0.046 and RR 0.347). Thisresearch concludes that there are correlation between breastfeeding, occupation, nutritional status of infants and the incidence ofdiarrhea in babies. Breastfeeding is the most influential factor in the incidence of diarrhea in babies. Breastfeeding may lower theincidence of diarrhea in babies.